2015
DOI: 10.1371/journal.pone.0122958
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thyroid Diseases with Primary Extra-Thyroidal Malignancies in Women: Results of a Cross-Sectional Study of 6,386 Patients

Abstract: We here analyzed the prevalence of extra-thyroidal malignancies (EM) in 6,386 female patients affected by different thyroid disease (TD). At first, an age-matched analysis of EM in all patients was performed. We then evaluated EM prevalence in four TD diagnostic categories: non-nodular TD (n = 2,159); solitary nodule (n = 905); multinodular TD (n = 2,871); differentiated thyroid cancers (n = 451). Finally, patients were grouped based on the absence (n = 3,820) or presence of anti-thyroglobulin (TgAb) and/or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 39 publications
(48 reference statements)
1
36
0
1
Order By: Relevance
“…DTC was associated with significantly higher risk (OR 12.2), most pronounced in the age 0 to 44 (OR 23.8). [ 2 ] We found only 2 reports in the English literature reporting simultaneous DTC and NHL. Rizkallah et al [ 3 ] reported similar case, whereas Singh et al [ 4 ] published recently a case with triple malignancies—laringeal cancer, DTC, and NHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTC was associated with significantly higher risk (OR 12.2), most pronounced in the age 0 to 44 (OR 23.8). [ 2 ] We found only 2 reports in the English literature reporting simultaneous DTC and NHL. Rizkallah et al [ 3 ] reported similar case, whereas Singh et al [ 4 ] published recently a case with triple malignancies—laringeal cancer, DTC, and NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, as cited by Prinzi et al, [ 2 ] attempted to explain the link between DTC and extra-thyroid malignancy implicating that “the long-term carcinogenic effects of specific cancer treatments might be responsible for a second cancer.” However, in our case there were synchronous occurrence of 2 malignancies and the most plausible explanation is the presence of yet unidentified molecular link or presence of general vulnerability carrying a higher risk for malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with thyroid disease (TD) and abnormal TSH levels, including on-nodular TD, solitary nodules, multinodular TD, thyroid cancers [with either the presence or absence of anti-thyroglobulin (TgAb)], and anti-thyroid peroxidase (TPOAb) or anti-thyroid-stimulating hormone (TSH) receptor autoantibodies, are at higher risk of developing kidney cancer (OR=3.40) compared to the general population (51). whereas, hypothyroidism is associated with longer progression-free survival (PFS) in sunitinib and sorafenib treatments (25,28).…”
Section: Thyroid-stimulating Hormone (Tsh)mentioning
confidence: 99%
“…In molecular research, disturbances in the 3,5,3'-triiodotyronine (T3) signaling pathway were described as a possible trigger in RCC (4). In clinical reports, an increased risk of kidney cancer was reported in women with a history of hypothyroidism with myxedema, thyrotoxicosis (5) or multinodular thyroid disease (6). The molecular background of coincidence or codependence of renal cell cancer and thyroid disease is elusive.…”
Section: Introductionmentioning
confidence: 99%